Association of Mean Platelet Volume / Platelet Count Ratio with Clinical Severity and Infarct Volume in Patients with Acute Ischemic Stroke - Nayyar, Muhammad Wasi; Mahmood, Asad; Liaqat, Jahanzeb; Robert, Helen Mary; Mahmood, Rafia; Khurshid, Ayesha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To examine the clinical severity and infarct volume of acute ischemic stroke (AIS) compared to control subjects by comparing the mean platelet volume/platelet count (MPV/PC) ratio. Study Design: Cross-sectional (validation) study. Place and Duration of Study: Acute Stroke Unit, Pak Emirates Military Hospital (PEMH), Rawalpindi, from Jul and Dec 2020. Methodology: This study included 50 consecutive AIS patients (Group-1) and 50 healthy subjects (Group-2). An automated haemanalyser determined MPV and MPV/PC ratios. In addition, a modified Rankin Scale for the severity of AIS and ABC/2 method for infarct volume was used. Results: This study comprised 69 males and 31 females. Statistical analysis showed that MPV and MPV/PC have significantly different mean values between Group-1 and Group-2 at a p-value of 0.001. In addition, according to the Rankin scale, a significant difference of means (p-value <0.001) of MPV and MPV/PC ratio was present between stroke patients with different infarct sizes. A higher CVA score per Rankin scale was associated with greater infarct size and higher MPV and MPV/PC values. Conclusion: Higher MPV and MPV/PC ratios are related to AIS compared to healthy individuals. Even greater MPV and MPV/PC ratio values are associated with increased infarct size. MPV and MPV/PC ratio measurements are simple, rapid, and highly cost-effective laboratory markers for risk stratification and early detection of cerebrovascular stroke.